Apakah latihan latihan meningkatkan hasil passing overhead bola voli pada pemain bola voli berusia 14-15 tahun? - Hermaya, Alin Danisa; Muslimin, Muslimin; Septiliza, Dewi; Fikri, Aprizal; Prastio, Dwi Seva (Universitas Nusantara PGRI Kediri, 2024)
Mastery of overhead passing techniques is still low because the lack of drill training models has resulted in the mastery of passing techniques not increasing. This research aims to determine the results of a drill training model to improve the passing results of amateur teenage volleyball players aged 14-15 years. The method used in this research is quasi-experimental, with a one-group pre-post test design approach. The population in this study consisted of 15 people, consisting of 10 boys and 5 girls aged 14-15 years, as well as amateur youth volleyball players aged 14-15 years, using saturated sampling techniques. The instruments or tools used in this research are tests and measurements, namely overhead passing ability tests. The method of collecting student data can be seen when students pass over the wall for 1 minute. Data analysis was carried out using the SPSS version 22 software method through the stages of data normality test, homogeneity test, and t-test. Based on the findings of this research, tcount -5.172 > ttable 1.761, with a significance value of 0.000 <0.05. Therefore, the results of the t-test in this study are significant. Using the drill training model effectively improves the passing results of amateur teenage volleyball players aged 14-15 years.